2007
DOI: 10.1158/1078-0432.ccr-07-1432
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Role of HuR in Hereditary Breast Cancer

Abstract: Purpose: HuR is an mRNA-binding protein that enhances the stability of certain transcripts and can regulate their translation. Elevated cytoplasmic expression of HuR protein has been linked to carcinogenesis and is associated with reduced survival in breast, ovarian, and gastric adenocarcinomas. Experimental Design: Here, we have explored the relevance of HuR in familial breast cancer. Tumor samples were collected from patients with identified BRCA1 (n = 51) or BRCA2 (n = 47) mutations or familial non-BRCA1/2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
79
0
5

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(91 citation statements)
references
References 33 publications
7
79
0
5
Order By: Relevance
“…In addition, our results are in accordance to several previously published studies [23][24][25][26][27][28][29][30][31]. In fact, a clinical study conducted on 97 ductal breast carcinoma patients revealed significant associations between elevated total HuR expression (calculated from the combination of staining intensity and extent of positivity in tumor cells) and advanced tumor histological grade and HER2-negative status [23].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In addition, our results are in accordance to several previously published studies [23][24][25][26][27][28][29][30][31]. In fact, a clinical study conducted on 97 ductal breast carcinoma patients revealed significant associations between elevated total HuR expression (calculated from the combination of staining intensity and extent of positivity in tumor cells) and advanced tumor histological grade and HER2-negative status [23].…”
Section: Discussionsupporting
confidence: 92%
“…Enhanced HuR expression and cytoplasmic localization have been associated with malignant phenotype and poor patients' prognosis in several human malignancies [18,22]. Interestingly, several studies have further suggested that HuR is implicated in malignant transformation of the breast, however, contradictory data have currently been reported regarding its clinical and prognostic impact in this type of neoplasia [23][24][25][26][27][28][29][30][31]. In view of the above considerations, the present study is aimed to evaluate the immunohistochemical expression of HuR and COX-2 in invasive breast carcinoma in association with multiple clinicopathological characteristics, tumor cells' proliferative capacity and ER, PR and HER2 expression, as well as overall and disease-free patients' survival.…”
Section: Introductionmentioning
confidence: 99%
“…The published data has both indicated that HuR overexpression correlates with increased as well as decreased aggressiveness in breast cancer. 23,24,43 These results would lend credence to the idea that HuR may be directing Biosciences) and analysis was performed using Cell Quest software (BD Biosciences).…”
Section: Methodsmentioning
confidence: 63%
“…[18][19][20][21][22] Increased HuR cytoplasmic expression directly correlates with severity and aggressiveness of many cancers, including those of the breast. [23][24][25] HuR has been demonstrated to be an important prognostic factor in familial breast cancer patients. 23,24 Recently, investigators altered the subcellular distribution of HuR and documented a decrease in mRNA stability, subsequent ER levels and susceptibility to tamoxifen.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation